Thermal analysis of friction stir processing (FSP) using arbitrary Lagrangian-Eulerian (ALE) and smoothed particle hydrodynamics (SPH) meshing techniques Thermische Analyse einer Rührreibverarbeitung mittels beliebiger Lagrange-Euler- und geglätteter Partikel-Hydrodynamik-Vernetzungstechniken - Meyghani, B. (Wiley-VCH Verlag, 2020)
Friction stir processing (FSP), a derivation of friction stir welding (FSW) is a material processing method which is used to locally modify the microstructure and texture of a given material. In friction stir processing (FSP), the heat produced by the frictional force and material deformation plays a significant role in producing a good surface quality. Therefore, the thermal modeling of friction stir processing (FSP) requires accurate boundary conditions and an appropriate mesh modelling technique. In this study, the thermal behavior of friction stir processing (FSP) using the aluminum alloy 6061-T6 for different process parameters is investigated. To solve complicated governing equations, two finite element formulations have been utilized; i. e. an arbitrary Lagrangian-Eulerian (ALE) and a smoothed particle hydrodynamics (SPH). For the arbitrary Lagrangian-Eulerian (ALE), a three-dimensional (3D) fully coupled thermomechanical finite element model using a modified Coulomb friction and Johnson-Cook material law has been used. The results show that, the temperature behavior is asymmetrical in the cross section and the peak temperature is approximately around 60Â â80Â of the melting temperature of the AA6061-T6. Moreover, it is seen that as the rotating velocity increases, the peak temperature is also increased; and the peak temperature decreases as the transverse speed increases. Finally, a good correlation between the calculated values and the literature is found. Â© 2020 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim